Obesity and periodontitis: a comprehensive review of their interconnected pathophysiology and clinical implications - Reytor-González, Claudia; Parise-Vasco, Juan Marcos; González, Natali; Simancas-Racines, Alison; Zambrano-Villacres, Raynier; Zambrano, Ana Karina; Simancas-Racines, Daniel (Frontiers in Nutrition, 2024)
Obesity and periodontitis are significant health problems with a complex bidirectional relationship. Excess body fat is linked to systemic diseases and can lead to persistent inflammation, potentially harming periodontal health. Periodontitis, a chronic inflammatory condition affecting the supporting structures of teeth, poses substantial health risks. Both conditions share pathological processes such as inflammation and oxidative stress, which aggravate health status and make treatment more challenging. Understanding this interaction is crucial for developing effective management strategies for both diseases. This study explores the multifaceted aspects of obesity and periodontitis and their reciprocal relationship.